Analysis of Social Media Perceptions Among Orthopaedic Surgery Residency Applicants and Social Media Use by Residency Programs During the 2020 to 2021 Cycle. Issue 4 (21st October 2021) - Checketts, Jake X.; Hunt, Tyler; Checketts, Beaun R.; Scott, Jared T.; Johnson, Mark; Boose, Marshall; Schwartz, Mark; Chalkin, Brian
Abstract : Introduction: Owing to the coronavirus 2019 pandemic limiting both applicants and residency programs in their ability to connect in-person, it is likely that a shift toward virtual connections was made. We aimed to query applicants regarding their perspectives of orthopaedic residency program social media use. Furthermore, we aimed to quantify the number of orthopaedic surgery residency programs with active social media accounts. Methods: All applicants to a single orthopaedic surgery residency were surveyed regarding their perceptions of social media use by orthopaedic surgery residency programs. After this, we evaluated social media use by orthopaedic surgery residency programs. Results: Of total, 54.3% of applicants indicated that an orthopaedic surgery residency program they followed on social media posted content that increased their interest in the program. Furthermore, 77.8% of the applicants believed that orthopaedic surgery residency programs should have social media accounts, specifically Instagram. Of the orthopaedic surgery residencies identified, 113 (58.9%) had Instagram, 84 (43.8%) had Twitter, and 21 (10.9%) had Facebook accounts. Discussion: Applicants largely feel that orthopaedic surgery residencies should have social media accounts. Orthopaedic surgery residencies saw the value in connecting with students virtually, as shown by nearly 90% of the programs, with social media starting their accounts this year.